Zirconolite and xenotime U-Pb age constraints on the emplacement of the Golden Mile Dolerite silland gold mineralization at the Mt Charlotte mine, Eastern Goldfields Province, Yilgarn Craton, Western Australia. - Rasmussen, Birger; Mueller, A.; Fletcher, Ian (Springer, 2009)
In situ SHRIMP U-Pb dating of magmatic zirconolite (CaZrTi2O7) in the Golden Mile Dolerite from the Mt Charlotte gold deposit (Yilgarn Craton, Australia) has yielded the first robust emplacement age (2,680 9 Ma) for the principle host-rock of gold mineralization in the Kalgoorlie district. In contrast, comagmatic zircon gave ages from approx 2.68 Ga to approx 2.17 Ga, reflecting isotopic resetting of high-U and -Th crystals. In situ SHRIMP analysis of hydrothermal xenotime (YPO4), which co-exists with gold in alteration pyrite, provided a Pb/Pb isochron age of 2,655 13 Ma. This date indicates that the youngest deposit in the Kalgoorlie district (Mt Charlotte) formed at approx 2.65 Ga, and provides a new minimum age for the structurally older Golden Mile deposit. Our results indicate that gold mineralization at Mt Charlotte is approx 50 million years older than indicated by recent 40Ar/39Ar dating and places new constraints on the timing of late-stage regional faulting (D4) in the province.